Comparison of Rifamycins for Efficacy Against Mycobacterium avium Complex and Resistance Emergence in the Hollow Fiber Model System - Boorgula, Gunavanthi D.; Jakkula, Laxmi U. M. R.; Gumbo, Tawanda; Jung, Bockgie; Srivastava, Shashikant (Frontiers in Pharmacology, 2021)
Rifamycins are integral part of the combination regimen for treatment of pulmonary Mycobacterium avium-complex [MAC] infection, but different practitioners prefer different rifamycins. The objective of the study was to compare microbial kill and resistance emergence of rifamycins using principles of pharmacokinetics/pharmacodynamics. First, we identified rifamycin MICs in 20 MAC isolates from patients followed by concentration-response studies in test-tubes. Next, we examined efficacy and resistance suppression of three doses of each rifamycin in the hollow fiber system model of pulmonary MAC [HFS-MAC], mimicking human like concentration-time profile of the drugs. HFS-MAC units were repetitively sampled for total and drug-resistant MAC burden and for drug concentration measurements. Inhibitory sigmoid E max model, linear regression, and analysis of variance was used for data analysis. For rifabutin 90% of isolates had MIC<0.125 mg/L while for both rifampin and rifapentine this was <2.0 mg/L. There was no statistically significant difference [p>0.05] in maximal kill and effective concentration mediating 50% of the bacterial kill for among three rifamycins in the static concentration experiment. In the HFS-MAC, the bactericidal kill [day 0-4] for rifampin was 0.89 [95% Confidence Interval (CI): 0.43-1.35], for rifapentine was 1.05 [95%CI: 0.08-1.23], and for rifabutin was 0.92 [95%CI: 0.61-1.24] log 10 CFU/mL, respectively. Rifamycins monotherapy failed after just 4-days of treatment and entire MAC population was drug resistant on day 26 of the study. There was no dose dependent difference in MAC kill or resistance suppression among the three rifamycins tested in the HFS-MAC. Therefore, replacing one rifamycin, due to emergence of drug-resistance, with other may not be beneficial in clinical setting.